DEVELOPMENT OF BLOOD-PRESSURE AND CARDIAC REFLEXES IN THE FROG PSEUDIS-PARADOXSUS - Burggren, W. W.; Bicudo, J. E.; Glass, M. L.; Abe, Augusto Shinya [UNESP] (Amer Physiological Soc, 1992)
Systemic arterial blood pressure and heart rate (f(H)) were measured in unanesthetized, unrestrained larvae and adults of the paradoxical frog, Pseudis paradoxus from São Paulo State in Brazil. Four developmental groups were used, representing the complete transition from aquatic larvae to primarily air-breathing adults. f(H) (49-66 beats/min) was not significantly affected by development, whereas mean arterial blood pressure was strongly affected, being lowest in the stage 37-39 larvae (10 mmHg), intermediate in the stage 44-45 larvae (18 mmHg), and highest in the juveniles and adults (31 and 30 mmHg, respectively). Blood pressure was not significantly correlated with body mass, which was greatest in the youngest larvae and smallest in the juveniles. In the youngest larvae studied (stages 37-39), lung ventilation was infrequent, causing a slight decrease in arterial blood pressure but no change in heart rate. Lung ventilation was more frequent in stages 44-45 larvae and nearly continuous in juveniles and adults floating at the surface. Bradycardia during both forced and voluntary diving was observed in almost every advanced larva, juvenile, and adult but in only one of four young larvae. Developmentally related changes in blood pressure were not complete until metamorphosis, whereas diving bradycardia was present at an earlier stage.
Keywords: CIRCULATION; HEART RATE; DIVING REFLEXES